Persuasive Communication Approach in Preserving the Art of Rudat Aik Dewa in Aik Dewa Village, Pringgasela District, East Lombok Regency - Ibnu Fathony (Busyro: Jurnal Dakwah dan Komunikasi Islam, 2025)
Indonesia is known as an archipelagic nation rich in cultural heritage and traditional arts. This diversity is a priceless national asset, but it faces preservation challenges amidst modernization and globalization. The research method used is a qualitative case study in Aik Dewa Village, analyzing persuasive communication in the preservation of Rudat Art, a traditional Islamic art that is threatened by modernization. The persuasive strategy implemented is holistic and adaptive, including internal dialogue, intensive collaboration with schools (PAUD-SMP), and early regeneration from preschool age, as well as the instillation of Islamic moral and spiritual values. The response from the community, especially Generation Z, was found to be positive and participatory (for example in Rudat Kolosal), demonstrating the effectiveness of communication. This success is supported by Rudat's sacred value (ethos) and the credibility of local actors (Rudat Al-Guri). However, the main obstacle is the invasion of digital media, which causes apathy. In conclusion, the sustainability of preservation depends on the ability of communicators to optimize promotional adaptations on digital platforms to remain relevant to the younger generation.